A new approach to coat PA12 powders with laser-generated nanoparticles for selective laser sintering - Hupfeld, Tim; Laumer, T.; Stichel, T.; Schuffenhauer, T.; Heberle, Johannes; Schmidt, Michael; Barcikowski, S.; Goekce, B. (Procedia CIRP, 2018)
The modification of selective laser sintering (SLS) powder materials by nanoadditives offers the possibility to adapt the powder properties to the laser sintering process or the resulting part properties. To avoid agglomeration of the nanofiller, a new approach in which surfactant-free laser-generated colloidal nanoparticles are adsorbed onto the polymer surface directly in an aqueous solution is demonstrated. Based on this novel approach, polyamide 12 (PA12) powders are decorated with metal and oxide nanoparticles and processed via SLS. Electron microscopy and confocal laser scanning imaging are utilized to analyze the dispersion of the filler.
Created from Fastlane, Scopus look-up
Keywords: Laser additive manufacturing; Nanoparticles; Polymer powders; Pulsed laser ablation in liquids; Selective laser sintering